PERBEDAAN PERSEPSI ETIS MAHASISWA AKUNTANSI TERHADAP PRAKTIK EARNINGS MANAGEMENT (Studi Kasus pada Universitas Diponegoro) - Nurul Khanifah; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2020)
This research aims to find out whether there is a perception difference in Diponegoro University students toward earnings management practice based on 5th and 7th term and based on gender. The method for gathering data is questionnaires, in which data is gathered by a series of written questions answered by participants. Students asked for response samples are those who have learned Business Ethics, Cost Accounting, Management Accounting, Auditing 1, Auditing 2 and Theory Accounting. The total of participants are 100 Accounting students. Two-Way ANOVA is used as an analytical device.The results are as follows: 1.) First test results shows that there is significant perception difference in students who have learned Business Ethics, Cost Accounting, Management Accounting, Auditing 1, Auditing 2 and Theory Accounting. 2.) Second test result shows that there is significant difference between male and female students.